2018
DOI: 10.4081/thal.2018.7479
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Complications

Abstract: This work is licensed under a Creative Commons Attribution 4.0 License (by-nc 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…A meta-analysis showed that the prevalence of diabetes mellitus, impaired fasting glucose, and impaired glucose tolerances was 6.54%, 17.21%, and 12.46%, respectively [13]. It is another specified type of diabetes, although it shares the insulin deficiency of type 1 and resistance of type2 diabetes [14]. It is common in inadequately iron chelated patients, but is also seen in well transfused and regularly chelated patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis showed that the prevalence of diabetes mellitus, impaired fasting glucose, and impaired glucose tolerances was 6.54%, 17.21%, and 12.46%, respectively [13]. It is another specified type of diabetes, although it shares the insulin deficiency of type 1 and resistance of type2 diabetes [14]. It is common in inadequately iron chelated patients, but is also seen in well transfused and regularly chelated patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Hypothyroidism is a prevalent endocrine complication in TM, which occurs more frequently in the second decade of life [16]. The spectrum of thyroid dysfunction in patients with TM ranges from subclinical hypothyroidism (the most prevalent abnormality) to primary as well as secondary hypothyroidism [14]. Thyroid dysfunction arises mostly due to gland infiltration, direct iron cytotoxicity, chronic tissue hypoxia, free radical injury and organ siderosis.…”
Section: Thyroid Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the introduction of regular blood transfusion and before the availability of iron chelation therapies β-thalassemia major patients died within the first few years [2,3] . This bad prognosis changed since the survival rates, and life expectancy started to improve progressively and patients may survive until 4 th -5 th decades due to the implementation of continuous and significant advent of diagnostic and therapeutic method, consisting mainly of an intensive transfusion program combined with chelation regimes and imaging method [4,5,6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…The most serious disadvantage of life-saving transfusions is the inexorable accumulation of iron within tissues and high incidence of endocrine abnormalities in children, adolescents and young adults [4,5] .…”
Section: Introductionmentioning
confidence: 99%